The impact of Electric Train System (ETS) on air and road transportation / Wan Mazlina Wan Mohamed - Wan Mohamed, Wan Mazlina (Universiti Teknologi MARA, 2023)
The development of effective and efficient public transportation services is crucial in order to attract more people to use public transport, as visualized by the Land Public Transport Agency or known as Agensi Pengangkutan Awam Darat (APAD) to have 60 percent of Malaysian citizens travel using public transport. This will greatly aid the purpose of overcoming the issue of traffic congestion in Malaysia. Thus, this research aims to determine the best value offered to the customers in terms of travel time, fare, and comfort by performing a survey using questionnaires on citizens that uses public transportation, which is then analyzed using the Chi-Square test, Kaiser-Meyer-Olkin (KMO) and Bartlett's test, and Rotated Factor Matrix. Results from the analysis show that for a short distance, ETS and express bus provide the most value to their customers while air travel is preferable for long distance given the low travel time despite the travel cost. Value perception also varies based on the age given that young travelers put more emphasis on a low fare while older travelers value low travel time. Finally, other factors such as travel comfort, availability, and safety are gaining more awareness in value when choosing travel options hence these factors should not be ignored when operating a public transportation service.